Design of a cavity backed spiral antenna with improved pattern symmetry - Mohamad, Sarah Yasmin; Cahill, Robert; Fusco, Vincent (2013)
In this paper we investigate the azimuthal pattern symmetry of an Archimedean spiral antenna which is designed to operate over the frequency range 3-10 GHz. The performance of the spiral in free space is compared with a structure that is backed by a perfect electric conductor with a separation distance of λ/4 at the operating frequencies. The latter arrangement exhibits a higher gain, however it is observed that the radiation patterns are less symmetrical about boresight and this performance degradation increases with frequency. The predicted 3 dB beamwidth difference is shown to vary between 14° (3 GHz) and 51° (10 GHz). An improved antenna design is described which reduces the pattern asymmetry to ≈ 2° at 10 GHz. The reduction in modal contamination is obtained by inserting slots carefully arranged in a radial pattern to disrupt the surface currents that flow on the ground plane of the antenna.